IMPLEMENTASI MODEL WATERFALL PADA SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMK PERTANIAN KARAWANG - Eka Fitriani; Dede Firmansyah; Riska Aryanti; Walim Walim (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2018)
The development of the number of students that continues to grow from year to year, demands accuracy and accuracy in providing accurate and accurate information to students without the same repetition of data. Management of academic information at the Agricultural SchoolKarawang is done with the context of manual and paper use as data storage and archiving media including value data, schedule data subjects and other academic information so that it raises several problems in terms of timeliness of value recapitulation and making inefficient schedules. The existence of these problems, the authors make a website-based application scheme design with the waterfall method, a website-based academic information system can manage academic information on the school both value and schedule data subjects that can be updated regularly and stored in the database so that it can process information effective and efficient. The web-based academic information system is very useful in providing convenience to both teachers and students. The Web-Based Academic Information System is the right solution to realize an information system that is effective and efficient in helping with the presentation of information that will be channeled or information to students.